Upcycling Polymeric Waste into Interpenetrating Polymer Network Adsorbents for Sustainable Wastewater Treatment - Ghayda Yaseen Al Kindi; Rana J. Kadhim; Elaf Abd Al-Azal Ihsan; Sinan A. Al-Haddad (Bumi Publikasi Nusantara, 2026)
This study reports the sustainable synthesis, characterization, and application of Interpenetrating Polymer Networks (IPNs) derived from post-consumer polystyrene kitchenware and epoxy resin residues as a cost-effective adsorbent for amoxicillin removal from wastewater. The conversion of these polymeric wastes into functional materials aligns with circular economy strategies. Batch adsorption experiments were carried out to examine the effects of key operational parameters, including adsorbent dosage, contact time, and solution pH. The results showed a maximum removal efficiency (96%) at an adsorbent dosage of 0.1 g and pH 5. Kinetic analysis indicated that the adsorption process followed a pseudo-second-order model, suggesting chemisorption as the dominant mechanism, with an equilibrium adsorption capacity (qe) of 8.13 mg/g. Isotherm modeling demonstrated that the Langmuir model provided the best fit, confirming monolayer adsorption on a homogeneous surface, while Temkin parameters indicated favorable adsorption energetics. Overall, these findings highlight the potential of waste-derived IPNs as eco-friendly and highly effective materials for removing pharmaceutical contaminants from aqueous environments, contributing to the advancement of sustainable wastewater treatment technologies.